Surface CH3NH3+ to CH3+ Ratio Impacts the Work Function of Solution‐Processed and Vacuum‐Sublimed CH3NH3PbI3 Thin Films. Issue 6 (1st February 2019) - Wang, Rongbin; Zhuo, Ming‐Peng; Li, Jitao; Zhai, Tianshu; Yang, Jiacheng; Fu, Keke; Liao, Liang‐Sheng; Liu, Lijia; Duhm, Steffen
Abstract: CH3 NH3 PbI3 thin films are fabricated using several representative synthesis methods such as spin‐coating, evaporation, and a combination of the two. These methods, which frequently occur in reported literatures, use the same precursors PbI2 and CH3 NH3 I but differ in how the two are mixed. It is found that the latter plays a vital role in determining the surface morphology, composition, and grain size of the films, even when the same stoichiometric ratio of the precursors is used. X‐ray photoelectron spectroscopy reveals that the amount of CH3 + ‐type defects, which results from CH3 NH3 I dissociation, is sensitive to both the physical state of CH3 NH3 I and the order of mixing sequence. The variation of the CH3 NH3 + :CH3 + ratio also affects the valence band and the work function of the corresponding films, as revealed by ultraviolet photoelectron spectroscopy. Furthermore, the energy‐level alignment between the perovskite film and a model hole transport layer, N, N′‐di(1‐naphthyl)‐N, N′‐diphenylbenzidine (NPB) is examined. It is found that the CH3 NH3 + :CH3 + ratio correlates with the offsets between the valence band maximum of perovskite film and the highest occupied molecular orbital of NPB as well, and the energy‐level alignment with the dual‐source, coevaporated CH3 NH3 PbI3 film is most suitable for efficient hole transport. Abstract : The surface cation ratio between CH3 NH3 + and CH3 +, for which the CH3 + ‐type defects result from CH3 NH3 I dissociation, has a clear impact on the work function of CH3 NH3 PbI3 perovskite films fabricated by different methods, and controls the energy‐level alignment with charge transport layers.